Comparing a Thai Words Segmentation Methods in the LST20 Dataset - Krittapol Damrongkamoltip; Khatcha Ruenlek; Wasit Limprasert; Prachya Boonkwan (Journal of Computer and Creative Technology)
In this era of globalization where information is widely available, organizations are increasingly placing importance on using information to enhance their business. Although data is easily available, there are still challenges in natural language processing tasks, especially, the division of Thai words that lacks clarity of word boundaries, etc. This makes it difficult to identify the word groups in a sentence appropriately. Therefore, this study focuses on evaluating the performance of the word segmentation method including the Dictionary use and learning from data using evaluation of word segmentation in six techniques are important goals for the verification of the literal level accuracy and processing time of each method and technique, by the LST20 dataset contains 3,745 documents and covers 15 news categories in results show a more efficient way to learn from data.